Registration of 'SB255' winter barley. Issue 2 (6th May 2021) - Brooks, Wynse; Griffey, Carl; Vaughn, Mark; Seago, John; Thomason, Wade; Fitzgerald, Joshua; Christopher, Anthony; Pitman, Robert; Dunaway, David; Light, Jon; Rucker, Elizabeth; Behl, Harry; et al.
Abstract: 'SB255' (Reg. no. CV‐373, PI 693987) is a six‐rowed hulled barley ( Hordeum vulgare L.) cultivar with winter growth habit. The cultivar was released by the Virginia Agricultural Experiment Station in May 2019. SB255 is widely adapted, high yielding, high grain volume weight, and medium tall. It has good winterhardiness and good straw strength. The spikes of SB255 are strap and slightly waxy with no overlapping lateral kernels and with long awns. Prior to being named, SB255 was tested under the experimental designation VA11B‐141 (LA). It was derived from the cross Spont03‐44/VA01B‐44 and developed using a modified‐bulk breeding method. It was evaluated from 2013 to 2019 in the Virginia Official Variety Trials at five to six locations. SB255's average grain yield (5, 214 kg ha –1 ) was similar to the check cultivars 'Secretariat' and 'Thoroughbred' but significantly ( P ≤ .05) higher than 'Atlantic', 'Price', 'Callao', 'Nomini', and 'Wysor'. Average grain volume weight of SB255 (60.8 kg hL –1 ) was similar to Secretariat and Price but exceeded ( P ≤ 0.05) those of Thoroughbred, Atlantic, Callao, Nomini, and Wysor. Head emergence of SB255 was similar to Thoroughbred and 2–5 d later than winter feed barley cultivars Secretariat, Atlantic, Price, Callao, and Nomini. SB255 was developed primarily as a feed barley cultivar. It provides barley producers and end users in the eastern United States with a high‐grain‐yielding cultivar having good to moderate resistance to all diseases prevalent in the eastern United States, including Fusarium head blight (FHB), and also lower deoxynivalenol (DON) accumulation in the grain.